The Law of Divorce and It’s Impact According to the Psychological and Health Perspective - et al., Haeratun (International Journal of Advanced Science and Technology, 2019)
Legally, a husband or wife can file a divorce charge with just one legal reason among several existing legal reasons and is specified in Article 39 paragraph (2) of UUP Number 1 of 1974 and has been elaborated in Article 19 PP No. 9 of 1975, and it is emphasized that in addition to having to be done before a court hearing to realize the certainty of fair law and protect the wife and even the husband during and after the divorce law process, divorce is also not prohibited in the sense that the husband and wife may break marital relations between the two, on the grounds legal grounds that have been determined in applicable laws and regulations. There are several impacts arising from divorce that occur between husband and wife and offspring from both psychological and health perspectives, such as feelings of disappointment, stress, sadness, anger, trauma, decreased achievement, blame yourself and parents, and broken friendship ties between second families parties.